SOCIO-PSYCHOLOGICAL NATURE OF THE MILITARY TRAUMA OF ADOLESCENCES WHO WERE LEFT WITHOUT PARENTAL CARE AS A RESULT OF THE RUSSIAN-UKRAINIAN WAR - Лівандовська, Інна (SWorldJournal, 2024)
The study explores the social-psychological prerequisites of military trauma among adolescents who have been left without parental care as a result of the Russian-Ukrainian war. The characteristic psychological features of orphaned adolescents' military